Down Regulation of c-FLIPL Enhance PD-1 Blockade Efficacy in B16 Melanoma - Wang, Yao; Li, Jing-jing; Ba, Hong-jun; Wang, Ke-feng; Wen, Xi-zhi; Li, Dan-dan; Zhu, Xiao-feng; Zhang, Xiao-shi (Frontiers in Oncology, 2019)
Immune checkpoint blockade of programmed cell death protein 1 (PD-1) had an impressive long-lasting effect in a portion of advanced-stage melanoma patients, however, this therapy failed to induce responses in several patients; how to increase the objective response rate is very important. Cellular FLICE (FADD-like IL-1β-converting enzyme)-inhibitory protein (c-FLIP) is a master anti-apoptotic regulator and is also thought to be the main causal factor of immune escape. The overexpression of c-FLIPL occurs frequently in melanoma and its expression is associated with the prognosis. We found that the level of c-FLIPL expression was associated with the PD-1 blockade response rate in melanoma patients. Thus, we performed this research to investigate how c-FLIPL regulates immunotherapy in melanoma. We demonstrate that down regulation of c-FLIPL enhances the PD-1 blockade efficacy in B16 melanoma tumor model. Down regulation of c-FLIPL could increase the tumor apoptosis and enhance the antitumor response of T cells in the lymphocyte tumor cells co-culture system. Moreover, knockdown of c-FLIPL could decrease the expression of PD-L1 and recruit more effector T cells in the tumor microenvironment. Our results may provide a new combined therapeutic target for further improving the efficacy of PD-1 blockade in melanoma.